European integration and changing British discourse on sovereignty - Nakano, Minoru (2013)
This study investigates whether British elites’ discourse on sovereignty has changed as European integration has progressed. Academic research has long recognized the existence of discourse change regarding sovereignty, and the process of European integration is likely to be a modern event that produces such change in elite understanding of sovereignty. The dissertation thus investigates the question of whether elite discourse on sovereignty has indeed changed in the context of European integration. This research is separated into two parts. The first part examines how the academic literature has discussed sovereignty in the contemporary world, how sovereignty has generally been conceptualized in Britain and the challenge of European integration to the academic and British political debates around sovereignty thereby presenting the key mechanism behind modern discourse change. The second part conducts a discourse analysis focusing on statements of British MPs from British accession to the EC to the debate on the Treaty of Lisbon. In order to conduct discourse analysis, MPs are classified into specific groups: Government, the Conservative Party, the Labour Party, and those who favoured a bill, and those who were against a bill. Further, I divide the process of European integration into three time periods: the Accession to the EC and the referendum on membership (1971-1975); the Single European Act and the Treaty of Maastricht (1985-1993); and New Labour (1997-2009). The analysis is carried out by a comparison between different groups and time periods. Ultimately, the dissertation determines whether British elites’ discourse on sovereignty has changed and, if so, whether there is a new interpretation of sovereignty in modern day Britain.